Potential of miR-21 to Predict Incomplete Response to Chemoradiotherapy in Rectal Adenocarcinoma - Ourô, Susana; Mourato, Cláudia; Velho, Sónia; Cardador, André; Ferreira, Marisa P.; Albergaria, Diogo; Castro, Rui E.; Maio, Rui; Rodrigues, Cecília M. P. (Frontiers in Oncology, 2020)
Background: Patients with locally advanced rectal adenocarcinoma are treated with neoadjuvant chemoradiotherapy. However, biomarkers for patient selection are lacking and the association between miRNA expression and treatment response and oncological outcomes is unclear. Objectives: To investigate the miRNAs as predictors association between miRNA expression and of response to neoadjuvant chemoradiotherapy and its association with oncological outcomes. Methods: This retrospective study analysed miRNA expression (miR-16, miR-21, miR-135b, miR-145 and miR-335) in pre- and post-chemoradiation rectal adenocarcinoma tissue and non-neoplastic mucosa in 91 patients treated with neoadjuvant chemoradiotherapy (50.4Gy) and proctectomy. Two groups were defined: a pathological complete responders group (Tumour regression grade - TRG 0) and a pathological incomplete responders group (TRG 1, 2 and 3). Results: miR-21 and miR-135b were up-regulated in tumour tissue of incomplete responders comparing with non-neoplastic tissue (p = 0.008 and p < 0.0001, respectively). Multivariate analysis showed significant association between miR-21 in pre-chemoradiotherapy tumour tissue and response, with a 3.67 odds ratio (OR) of incomplete-response in patients with higher miR-21 levels (p = 0.04). Although with no significance, patients treated with 5-fluorouracil presented reduced odds of incomplete response compared with those treated with capecitabine (OR = 0.19; 95% confidence interval (CI) 0.03 - 1.12, p = 0.05). Moreover, significant differences were seen in overall survival in relation to clinical TNM stage (p = 0.0004), cT (p = 0.0001), presence of distant disease (p = 0.002), mesorectal tumour deposits (p = 0.003) and tumour regression grade (p = 0.04). Conclusion: miR-21 may predict response to chemoradiotherapy in rectal cancer.